Characterization of sound speed profile in Malaysian Sea - Abdirahim Kalif Ali Wardere, 1985-; Nor Hisham Khamis, 1965-; Fakulti Kejuruteraan Elektrik (2013)
Thesis (Master of Engineering (Electrical - Electronics & Telecommunications) - Universiti Teknologi Malaysia, 2013